Full-color phosphors from europium(III)-based organosilicates - Carlos, Luís D.; Messaddeq, Younés [UNESP]; Brito, Hermi F.; Sá Ferreira, Rute A.; De Zea Bermudez, Verónica; Ribeiro, Sidney J. L. [UNESP] (My University, 2000)
Room-temperature white light emission materials were synthesized using Eu3+-based hybrid xerogels. Color tunabability across the Commission Internationale de L'Eclairage (x,y) chromaticity diagram was obtained by changing the salt concentration and/or the excitation wavelength. The values of the Ω2 and Ω4 intensity parameters show a highly polarizable Eu3+ local environment. The existence of four available carbonyl oxygen at the salt concentration for each incorporated Eu ion accounts for the greater tendency of the first ligands to bond covalently to the metal ion. A gradual increase in the non-radiative channels as the salt concentration increases is due to the replacement of carbonyl oxygen by water molecules in the Eu3+ first coordination shells.